(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
There is a special bilateral relationship between India and Bangladesh due to the closeness of both countries, the past connections, the cultures and the economic interdependence. This relationship received a massive shift in the last twenty years with the transformation of the political leadership, the geopolitical situation in the region, and the growing economic collaboration. The current research is a critical analysis of the political, economic, and security aspect in relations between India and Bangladesh in the time frame of 1999-2019. The research was done using a qualitative and analytical research design that relied on secondary data through government reports, policy documents, bilateral agreements, scholarly publications and international databases. The discussion reveals the major trends including the adoption of the Land Boundary Agreement that happened in 2015, the growth of bilateral trade, regional connectivity, and strengthened collaboration in counter-terrorism and border control. The results show that the level of political involvement in the two countries also became much better since 2009, which contributed to the growth of diplomatic collaboration and mutual trust. Another significant development was an extension of economic relations between the two countries, as bilateral trade increased and several connections and energy projects enhanced integration in the region. Moreover, security relations between the two countries were enhanced as the countries worked together in fighting insurgency, border management, and intelligence exchange. Despite these positive developments, certain challenges such as trade imbalance, water-sharing disputes, and migration issues continue to influence bilateral relations. The research concludes that the partnership between India and Bangladesh has been enhanced by political leadership, shared economic interests, and common security issues that make the relationship of both countries an important stabilizing factor and cooperation in South Asia.